2018
DOI: 10.1002/ep.13081
|View full text |Cite
|
Sign up to set email alerts
|

Use of DPSIR Framework to Analyze Water Resources in Qatar and Overview of Reverse Osmosis as an Environment Friendly Technology

Abstract: Qatar and other countries of Gulf Cooperation Council are among the most water scarce countries in the world and are being characterized as “high‐water risk” countries by Water Resource Institute. Therefore, it is important to implement sustainable water resource management that encompass economic, societal, and environmental aspects. In this review article, the Driver‐Pressure‐State‐Impact‐Response framework was used to analyze the water resource system in Qatar in terms of drivers, pressures, change in state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 98 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…In the process of increasing influence of human activities, the dynamic equilibrium status of water resources continues to change. When the influence exceeds the resilience threshold of the water resource system, the dynamic equilibrium will be broken, and a new equilibrium status will be formed in the system [37]. This framework provides an analysis tool to eliminate the adverse impact of human activities on water resources and improve water resource management measures because it better describes the water system in a process of dynamic change affected by human activities; specifically, it clearly considers what has happened (pressure), what has changed (status), what is the effect (effect), and the logic of human response (response) (Figure 2).…”
Section: Construction Of Pser Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of increasing influence of human activities, the dynamic equilibrium status of water resources continues to change. When the influence exceeds the resilience threshold of the water resource system, the dynamic equilibrium will be broken, and a new equilibrium status will be formed in the system [37]. This framework provides an analysis tool to eliminate the adverse impact of human activities on water resources and improve water resource management measures because it better describes the water system in a process of dynamic change affected by human activities; specifically, it clearly considers what has happened (pressure), what has changed (status), what is the effect (effect), and the logic of human response (response) (Figure 2).…”
Section: Construction Of Pser Theoretical Frameworkmentioning
confidence: 99%
“…In the 2001-2015 period, the amount of fertilizer used in cultivated land rose from 39.71 kg/hm 2 •year to 58.86 kg/hm 2 •year, an increase of 48.22%. The increase in consumption levels and changes in consumption type caused by socioeconomic development has led to the continuously increasing impact of domestic sewage and other factors on water resources [37]. In general, the sustained increase in economic development and pressures of social living standards in the pressure subgroup increased the pressure on water resource security.…”
Section: Analysis Of Changes In Water Resource Pressure Subgroupmentioning
confidence: 99%
“…Because of its unique advantages in identifying the relationship between economic and social operations and environmental sustainable development, it is widely used in water and soil resource utilization efficiency, regional ecological environmental safety, and soil conservation. Evaluation and decision-making in related fields such as utilization and sustainable agricultural development [11]. The DPSIR model identifies the interaction between economic and social development and the environment, and establishes a causal chain of "Driving(D)-Pressure(P)-State(S)-Impact(I)-Response(R)" between the two, revealing the way in which economic and social development affects the environment and the environment The state's response to human activities can effectively integrate issues between human activities, economic and social development, and resources and the environment.…”
Section: Dpsir Conceptual Framework Modelmentioning
confidence: 99%
“…A growing trend in the application of combined RO-UF plants for desalination at an industrial scale is reported by Ashfaq et al 2019. Some plants are reported here: Tuas, Singapore (Capacity: 318,000 m3/day; Year: 2013), Ashdod, Israel (Capacity: 275,000 m 3 /day; Year: 2013), Ajman, United Arab Emirates (Capacity: 115,000 m 3 /day; Year: 2012), Tangshan, China (Capacity: 110,000 m 3 /day; Year: 2012), Teshi, Ghana (Capacity: 60,000 m 3 /day; Year: 2014), Accra, Ghana (Capacity: 60,000 m 3 /day; Year: 2014), Red Sea Coast—Saudia Arabia (Capacity: 30,000 m 3 /day, Year: 2016), Gwangyang, South Korea (Capacity: 30,000 m 3 /day; Year: 2015) [63].…”
Section: Literature Analysis On the Microplastic And Its Removal Bmentioning
confidence: 99%